Is There a Retirement-Consumption Puzzle? Evidence Using Subjective Retirement Expectations - Haider, Steven J; Stephens, Melvin (The Review of Economics and Statistics, 2007)
Previous research finds a systematic decrease in consumption at retirement, a finding that is inconsistent with the life cycle/permanent income hypothesis if retirement is an expected event. In this paper, we use workers' subjective beliefs about their retirement dates as an instrument for retirement. After demonstrating that subjective retirement expectations are strong predictors of subsequent retirement decisions, we still find a consumption decline at retirement for workers who retire when expected. However, our estimates of this consumption fall are about a third less than those found when we instead rely on the instrumental variables strategy used in prior studies.